Progress on dietary therapy for gout and hyperuricemia - JIN Lei, WU Qianqian, ZHANG Xiaomin, GUO Jie, WANG Feng (Jichu yixue yu linchuang)
This review briefs the anti-hyperuricemia(HUA) mechanism of nutrition targeting the gut, such as the gut microbiota promoting the catabolism of purine and uric acid(UA), and increased its metabolites like uric acid. The review also summarizes the probiotics and prebiotics that have the effect of lowering uric acid targeting at the gut, providing reference and guidance for further research. In addition, this paper reviews the effects of various diets, such as the dietary approaches to stop hypertension(DASH) diet, the Mediterranean diet, and the low-purine diet, as well as the effects of individual foods including alcohol, coffee and tea, cherries, dairy products, fructose, and vitamin C on hyperuricemia and gout outcomes.